Frontotemporal Network Connectivity during Memory Encoding Is Increased with Aging and Disrupted by Beta-Amyloid - Oh, Hwamee; Jagust, William J. (The Journal of neuroscience, 2013)
Approximately 30% of cognitively normal older adults harbor brain β-amyloid (Aβ), a prominent feature of Alzheimer's disease associated with neural alterations and episodic memory decline. We examined how aging and Aβ deposition affect neural function during memory encoding of visual scenes using functional magnetic resonance imaging (fMRI) in humans. Thirty-six cognitively normal older people underwent fMRI scanning, and positron emission tomography with [ 11 C] Pittsburgh compound B to measure fibrillar brain Aβ; 15 young subjects were studied with fMRI. Older adults without Aβ deposition showed reduced regional brain activation (compared with young subjects) with decreased task-independent functional connectivity between parahippocampal gyrus and prefrontal cortex. In this network, task-related connectivity was increased compared with young subjects, and the degree of connectivity was related to memory performance. In contrast, older individuals with Aβ deposition showed no such increased task-related network connectivity, but did display increased regional activity unassociated with performance. These findings suggest that network connectivity plays a significant role in compensating for reduced regional activity during successful memory encoding in aging without Aβ deposition, while in those with Aβ this network compensation fails and is accompanied by inefficient regional hyperactivation.